Determinan Hipertensi di Puskesmas dan RSUD Kabupaten Natuna - Andayasari, Lelly; Opitasari, Cicih (Puslitbang Biomedis dan Teknologi Dasar Kesehatan, 2015)
Abstract The result of (Basic Health Research) in 2007 showed that the highest prevalence. To describe the hypertension patients in Public Health Centre and in District Hospital in Natuna.The study used cross sectional design. The samples were collected fromÂ all hypertension patients medical records in three Public Health Centre (Pulau Tiga, Sedanau and Ranai) and oneÂ hospital (RSUD Natuna) during the periode ofÂ January 1 toÂ December 31, 2012. Univariate analysiwas used to describe the patientâs characteristics.The 423 samples were collected from three Public Health Centre and district hospital. TheÂ proportion of hypertension in Public Health Centre and distric hospital was 73.5% and 26.5% respectively. The highest proportion of hypertension was found in female, married, low education, and unemployed subjects, both of Public Health Centre and district hospital. The youngest age was 28 years old, while the oldest was 92 years old with the average was 57 years old. The proportion of stage 2 hypertension were 62.1% in Public Health Centre and 81.2% in district hospital. The higest proportion of comorbid diseases that become end point of hypertension in the district hospital was stroke (41,1%), cardiac enlargement/ left ventricular hypertrophy/ LVH (19.6%), coronary heart disease/ CHD (9.8%). The highest proportion of risk factors that was found along with hypertension were hypercholesterolemia (20.5%) and diabetes (10.7%). Most of hypertension patients were in stage 2 category. Hypercholesterolemia and diabetes were more common risk factors to be found along with hypertension, furthermore stroke, cardiac enlargement/ LVH (19.6%) and CHD were the most common cardiovascular disease. Prevention of hypertension, screening and hypertension management to reduce hypertension complication need to be increased Keywords: Hypertension, Public Health Centre, District Hospital, Natuna District Abstrak Berdasarkan hasil Riskesdas 2007 prevalensi hipertensi di Kabupaten Natuna tertinggi di IndonesiaÂ mendeskripsikan penderita hipertensi di Puskesmas dan di RSUD di Kabupaten Natuna.Penelitian ini menggunakan rancangan cross sectional. Sampel adalah semua pasien hipertensi yang datang ke Puskesmas (Puskesmas Pulau Tiga, Sedanau dan Ranai) dan RSUD Natuna pada periode 1 Januariâ31 Desember 2012. Data dikumpulkan dari rekam medik penderita hipertensi kemudian dipindahkan ke dalam formulir pengumpulan data.Â Sebanyak 423 sampel diperoleh dari tiga puskesmas dan RSUD. ProporsiÂ hipertensiÂ di PuskemasÂ sebesar 73,5%Â dan di RSUD 26,5%. Proporsi hipertensi terbanyakÂ ditemukan pada perempuan,Â status menikah, tingkat pendidikan rendahÂ danÂ tidak bekerja di Puskesmas maupun di RSUD.Â Umur terendah pasien hipertensi adalah 28 tahun dan tertinggiÂ 92Â tahun denganÂ median 57 tahun.Â Pasien dengan hipertensi stage 2 didapatkan paling banyakÂ yaituÂ Puskesmas 62,1% danÂ RSUDÂ 81,2%.Â Proporsi penyakitÂ penyerta di RSUD terbanyakÂ adalah stroke 41,1% diikuti dengan pembesaran jantung 19,6% dan jantung koroner 9,8%.Penderita hipertensi paling banyak berada dalam kategori stage 2. Faktor risiko bersama hipertensi terbanyak adalah hiperkolesterol, dan diabetes sedangkan stroke, pembesaran jantung dan jantung koroner merupakan komplikasi kardiovaskuler terbanyak yang ditemukan. Upaya pencegahan dalam menurunkan kejadian hipertensi perlu ditingkatkan, begitu pula dengan deteksi dini dan penanganan hipertensi yang tepat untuk mengurangi komplikasi hipertensi. Â Kata kunci: Hipertensi, Puskesmas, RSUD